MULTIMEDIA INTERAKTIF BERBASIS STRATEGI EDULOCAL TOURISM UNTUK SISWA SEKOLAH DASAR - Andika Adinanda Siswoyo; Dicky Julian Pratama (UNIB Press, 2023)
This Riset to develop interactive multimedia products based on edulocal tourism. The integration of the concept of edulocal tourism with interactive multimedia is carried out by combining local tourism content on Jumiang Beach with student learning content. This research is an R&D type research using the Borg and Gall model which consists of 10 stages. The subjects used were fifth grade students at SDN Tanjung 3 Pamekasan. The results of this study indicate that edulocal tourism-based interactive multimedia development products obtain a validity percentage of 76% (valid). The attractiveness percentage of the teacher is 94% (very interesting) and students are 96% (very interesting). The effectiveness of the product is based on the percentage of observation of teacher activity 100% (very good), observation of student activity 90% (active) and the percentage of completeness of classical learning outcomes 88% (complete). Based on these results, interactive multimedia products based on edulocal tourism can help students understand learning material that requires learning media to improve learning outcomes, study enthusiasm, achieve the expected learning goals.